2019
DOI: 10.1177/1010539519870665
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Victimization Among School-Going Adolescents in Malaysia: Prevalence and Associated Factors

Abstract: This study aimed to assess the prevalence and factors associated with bullying victimization from a nationwide school-based survey among 27 458 students aged 13 to 17 years. The overall prevalence of having been bullied in the past 30 days was 16.2%; this decreased with age. Multivariate logistic regression analysis revealed that factors most strongly associated with bullying victimization were exposure to physical attacks (adjusted odds ratio [aOR] = 2.46, 95% confidence interval [CI] = 2.17-2.79), illicit dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
1
9

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 27 publications
4
25
1
9
Order By: Relevance
“…The available responses varied from 0 to 30 days. In line with previous studies (44,45), participants with a response of at least 1 day were considered bullying victims.…”
Section: Bullying Victimization (Dependent Variable)mentioning
confidence: 91%
“…The available responses varied from 0 to 30 days. In line with previous studies (44,45), participants with a response of at least 1 day were considered bullying victims.…”
Section: Bullying Victimization (Dependent Variable)mentioning
confidence: 91%
“…Tanto víctima como victimario suelen relacionarse al género masculino y uso de sustancias psicoactivas 19,20 . Otras líneas de investigación se han enfocado en los aspectos sociales involucrados en el surgimiento del acoso y violencia escolar, destacando algunas condiciones de riesgo como la pobreza, experiencias familiares, relaciones de pares, acceso a armas, consumo de alcohol y psicoactivos, y exposición a violencia en los medios de comunicación 21 .…”
Section: Introductionunclassified
“…En cuanto a los efectos o consecuencias del matoneo, la condición de víctima se encuentra estadísticamente relacionado a la internalización y externalización de problemas 24 que incluyen: bajos niveles de bienestar psicológico y adaptación social, altos niveles de estrés psicológico y a síntomas físicos (aumento de la presión arterial, dolor de cabeza) 25 . Además, aumenta el riesgo de sufrir depresión, trastornos de ansiedad, psicosis, autoagresión 3 , abuso de sustancias psicoactivas 26 , pensamientos e intentos suicidios, suicidios consumados 21 . En un estudio realizado en 123.227 preadolescentes y adolescentes de 28 países de Europa, América del Norte e Israel; mediante un cuestionario auto administra-Debido a la notable relación entre el acoso escolar y diversos factores como la disfuncionalidad familiar y el consumo de sustancias psicoactivas, se hace necesario la vigilancia y la aplicación de instrumentos que evalúen dichos aspectos.…”
Section: Introductionunclassified
“…Research has shown that many students have experienced traditional bullying victimization. A study indicated that the prevalence rates of being a victim of traditional bullying in the last month were 16.2% (2). The results of other studies demonstrated that about 30 to 50% of students were bullied at school (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%